(untitled) (Research, Society and Development, 2023)
This study was conducted on a stretch of terra firme of the remnant of secondary forest known as Gunma Ecological Park, located in the municipality of Santa Bárbara-PA, Eastern Amazon, Brazil, in which 20 plots of 20 x 25 m each were demarcated, totaling 1 sample hectare and inventoried all tree individuals with DBH ≥ 10 cm. The phytosociological parameters were analyzed and the species were characterized regarding the structural and functional attributes: floristic, horizontal structure, diametric, successional stage and conservation status of the tree species surveyed. A total of 394 individuals were sampled, represented by 96 species, distributed in 37 families and 75 genera. The Fabaceae family presented higher representativeness in species richness. For the number of individuals, the Lecythidaceae family was the most expressive. The species with the highest importance value index (IV%) in the sampled area was Eschweilera coriacea (DC.) S.A.Mori (white matamatá). The diametric distribution had the highest concentration in class I (10.0 Ͱ 47.2 cm), presenting a negative exponential distribution (characteristic of heterogeneous tropical forests). The late secondary species represented 50.53% of the community, while the pioneer species formed the smallest group (8.42%), presenting a mature stage. Six "vulnerable" species and one "endangered" species were recorded, corroborating for greater conservation. After analysis, it was considered that the forest remnant presents a stable condition of its state, even if environmental disturbances were observed, being indicative for the conservation of the remnant.